2012
DOI: 10.1016/j.jobcr.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carotid artery atheromatous plaques using digital panoramic radiographs with Doppler sonography as the ground truth

Abstract: Objectives: The objective of the study was to determine whether digital panoramic radiography is a reliable method to detect calcified carotid artery atheromatous plaques (CCAAP) as compared to ultrasonography.Study design: Digital panoramic radiographs were obtained from 50 patients who also underwent carotid ultrasound examination. The images were interpreted by trained maxillofacial radiologist for the presence or absence of calcified atheromatous plaques. The extent of carotid calcification on carotid ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The authors found that the panoramic radiographs had a sensitivity of 66.6%, and a positive predictive value of 45% was found for the detection of carotid artery calcifications in patients whose angiograms confirmed the presence of coronary artery disease and a sensitivity of 50% in patients with a normal angiogram 20 . However, the sensitivity and specificity reached 76% and 98% in digital panoramic X‐rays, respectively, in the portrayal of carotid artery calcifications 21 . In addition, a statistically significant association was found between the presence of ECACs in panoramic radiographs and the percentage of alveolar bone loss in patients with periodontitis 19 …”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the panoramic radiographs had a sensitivity of 66.6%, and a positive predictive value of 45% was found for the detection of carotid artery calcifications in patients whose angiograms confirmed the presence of coronary artery disease and a sensitivity of 50% in patients with a normal angiogram 20 . However, the sensitivity and specificity reached 76% and 98% in digital panoramic X‐rays, respectively, in the portrayal of carotid artery calcifications 21 . In addition, a statistically significant association was found between the presence of ECACs in panoramic radiographs and the percentage of alveolar bone loss in patients with periodontitis 19 …”
Section: Introductionmentioning
confidence: 99%
“…In 1981 Friedlander first unveiled the presence of soft tissue calcifications in this unvisited territory of panoramic radiographs (2,5). CCAAs are closely related to cerebrovascular accidents and such calcifications can be radiographically detected while performing routine medical procedures (11).…”
Section: Discussionmentioning
confidence: 99%
“…The PRs analysis investigated radiopaque images in the soft tissues compatible with images suggestive of CCAA. They were interpreted either as nodular or as verticolinear radiopacity below the mandibular angle, adjacent or inferior to the hyoid bone, epiglottis, and cervical vertebrae at, above, or below the intervertebral space of C3-C4, and at a 1.5-2.5-cm distance (1,2,7,10,12,16).…”
Section: Panoramic Radiographic Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability of digital panoramic radiographs in detecting atheroma in the carotid artery was assessed [69] and the authors compared with ultrasound examinations. The results showed that digital panoramic radiography has a high level of agreement with ultrasonography with 76% of sensitivity and 98.66% of specificity.…”
Section: Arterial Calcificationsmentioning
confidence: 99%